Disparities exist among US adolescents in the receipt of transition to adult healthcare services: the differential impact of social determinants of health, healthcare needs, and COVID-19 - Girdwood, Tyra C.; Silva, Susan G.; Maslow, Gary R.; Docherty, Sharron L. (Frontiers in Public Health, 2024)
IntroductionWe examined the influence of special healthcare needs, onset of the COVID-19 pandemic, and their interaction on receiving transition services to prepare for future adult care among US adolescents, and whether social determinants of health moderated the relationship of these factors with receiving transition services.MethodsWe analyzed the National Survey of Children's Health (2019, 2020–2021) using adjusted multivariable logistic regression models. We assessed a repeated cross-sectional, nationally representative sample of adolescents aged 12–17 years old. Sampling weights were used to generalize samples to the populations of interest. The main outcome was receipt of transition services to prepare for future adult healthcare. Measures included pre vs. post COVID-19 onset, special healthcare needs, and social determinants of health (health insurance, food sufficiency, neighborhood safety, household language, race/ethnicity, and household poverty level). Sex and two-parent households were included as covariates.ResultsA total of 45,935 adolescents were included, with N=12,230 in the pre COVID-19 group and N=33,705 in the post COVID-19 group. We found statistically significant higher odds of receiving transition services among adolescents with special healthcare needs (95 CI = 1.23, 1.58), females (95 CI = 1.09, 1.39), and during pre COVID-19 (95 CI = 1.14, 1.45). Private insurance (95 CI = 1.03, 1.37), English as primary household language (95 CI = 1.19, 2.27), and race/ethnicity were significant predictors of receipt of transition services. Neighborhood safety significantly moderated (95 CI = 1.70, 6.60) the relationship between special healthcare needs and receipt of transition services.DiscussionThis population-based study identified significant disparities in receipt of transition services provided to US adolescents via the differential impact of social determinants of health, special healthcare needs, and COVID-19 onset on receipt of services.